Generation ZAlpha : connecting with the next micro-generation. - Leyts, Maarten, ....- (Leuven : LannooCampus, 2023)
'Generation ZAlpha' is a playbook that guides you through the changes in marketing and communication to this micro-generation. The desire for more specific insights is what led to the notion of hybrid generations, or micro-generations. It will start you on a journey to understand the hopes, dreams, and aspirations of a unique cohort growing up with the experience of the pandemic who are poised to shape our future; the cohort that is at the cusp of being the youngest Gen Z and oldest Gen Alpha.
Keywords: Gen Z; Generation Z; Jongeren; Jongerencultuur